The Role of Entrepreneurship as the Driver of Economic Growth in India - Kashyap (Retd), Major Poonam (Digital Repository of Theses, 2024)
The goal of this study is to take a detailed look at the role of entrepreneurship in a country’s economic development. It also looks at the impact of entrepreneurial ventures on economic growth during periods of recession. Many studies have found a strong association between entrepreneurship and economic growth in developing countries in India, implying it to be a viable solution for India’s economic problems. It has been known that entrepreneurship fosters skills such as creative thinking, product development, marketing and leadership which results in flourishing micro, small and medium enterprises (MSMEs). Such enterprises diversify and increase India’s economic status. Studies have also discovered that India still relies on oil for more than 90% of its foreign exchange income. This stagnant reliance which hasn’t changed in ears has resulted in an economic crisis that requires significant economic diversification to be vanquished. Apart from entrepreneurship, other sectors of the economy like agriculture, mining and manufacturing should be actively developed to diversify the country’s foreign exchange earnings. A study has claimed that entrepreneurship identifies business prospects and scales them to enhance a nation’s economic development. Only a revolution comprising such enterprises can resolve India’s current economic crisis. This research analyses the opportunities created by entrepreneurial ventures and how they can positively impact India’s economic situation. By primarily focusing on MSMEs, their impact on both short and long-term contributions to economic growth.